Thermal properties and kinetics of new-generation posterior bulk fill composite cured light-emitting diodes - YILMAZ ATALI, PINAR (SPRINGER, 2014)
In this study, the thermal behavior in terms of glass transition (T (g)), degradation, and thermal stability of four commercial new-generation posterior bulk fill composites (Surefill SDR, Dentsply; Quixfill, Dentsply; Xtrabase, Voco; and Xtrafill, Voco) activated by light-emitting diodes (LEDs) was analyzed by thermogravimetric analysis (TG), differential scanning calorimetry (DSC), and dynamic mechanical analysis (DMA). The activation energies (E (a)) for the decomposition of the dental resins were calculated based on the Kissinger and Doyle kinetic models from the peaks of the endothermic curves obtained when the specimens were heated at four different temperatures (5, 10, 15, and 20 A degrees C min(-1)) during DSC. The results show that the Xtrabase composite displayed the highest T (g) (120 A degrees C at a 5 A degrees C min(-1) heating rate) and E (a) (157.64 kJ mol(-1)) values associated with thermal degradation from the main chain of the polymer.
Keywords: Posterior bulk fill composites; LED; TG; DSC; DMA; Kinetics; DENTAL RESTORATION COMPOSITE; RESIN-COMPOSITES; POLYMERIZATION SHRINKAGE; CONVERSION; STRESS; DEPTH; LEDS